"Don't wait for them to come to you, you go to them". A qualitative study of recruitment approaches in community based walking programmes in the UK. - Matthews, A; Brennan, G; Kelly, P; McAdam, C; Mutrie, N; Foster, C (BioMed Central, 2012)
Background: This study aimed to examine the experiences of walking promotion professionals on the range and effectiveness of recruitment strategies used within community based walking programmes within the United Kingdom. Methods: Two researchers recruited and conducted semi-structured interviews with managers and project co-ordinators of community based walking programmes, across the UK, using a purposive sampling frame. Twenty eight interviews were conducted, with community projects targeting participants by age, physical activity status, socio-demographic characteristics (i.e. ethnic group) or by health status. Three case studies were also conducted with programmes aiming to recruit priority groups and also demonstrating innovative recruitment methods. Data analysis adopted an approach using analytic induction. Results: Two types of programmes were identified: those with explicit health aims and those without. Programme aims which required targeting of specific groups adopted more specific recruitment methods. The selection of recruitment method was dependent on the respondent's awareness of 'what works' and the resource capacity at their disposal. Word of mouth was perceived to be the most effective means of recruitment but using this approach took time and effort to build relationships with target groups, usually through a third party. Perceived effectiveness of recruitment was assessed by number of participants rather than numbers of the right participants. Some programmes, particularly those targeting younger adult participants, recruited using new social communication media. Where adopted, social marketing recruitment strategies tended to promote the 'social' rather than the 'health' benefits of walking. Conclusions: Effective walking programme recruitment seems to require trained, strategic, labour intensive, word-of-mouth communication, often in partnerships, in order to understand needs and develop trust and motivation within disengaged sedentary communities. Walking promotion professionals require better training and resources to deliver appropriate recruitment strategies to reach priority groups.